Special Topics in Drug Discovery - Chen, Taosheng; Chai, Sergio C. (IntechOpen, 2016)
Drug discovery involves multiple disciplines, technologies, and approaches. This book selects important topics related to drug discovery, including emerging tool (Chapter 1), cutting-edge approaches (Chapters 2, 3, and 4), examples of specific therapeutic area (Chapter 5), quality control in drug development (Chapter 6), and job and career opportunities in the pharmaceutical sector, a topic rarely covered by other books (Chapter 7). This book draws knowledge from experts actively involved in different areas of drug discovery from both industrial and academic settings. We hope that this book will facilitate your efforts in drug discovery.